Effects and Mechanisms of 3α,5α,-THP on Emotion, Motivation, and Reward Functions Involving Pregnane Xenobiotic Receptor - Frye, Cheryl A.; Paris, Jason J.; Walf, Alicia A.; Rusconi, Jamie C. (Frontiers in Neuroscience, 2012)
Progestogens [progesterone (P4) and its products] play fundamental roles in the development and/or function of the central nervous system during pregnancy. We, and others, have investigated the role of pregnane neurosteroids for a plethora of functional effects beyond their pro-gestational processes. Emerging findings regarding the effects, mechanisms, and sources of neurosteroids have challenged traditional dogma about steroid action. How the P4 metabolite and neurosteroid, 3α-hydroxy-5α-pregnan-20-one (3α,5α-THP), influences cellular functions and behavioral processes involved in emotion/affect, motivation, and reward, is the focus of the present review. To further understand these processes, we have utilized an animal model assessing the effects, mechanisms, and sources of 3α,5α-THP. In the ventral tegmental area (VTA), 3α,5α-THP has actions to facilitate affective, and motivated, social behaviors through non-traditional targets, such as GABA, glutamate, and dopamine receptors. 3α,5α-THP levels in the midbrain VTA both facilitate, and/or are enhanced by, affective and social behavior. The pregnane xenobiotic receptor (PXR) mediates the production of, and/or metabolism to, various neurobiological factors. PXR is localized to the midbrain VTA of rats. The role of PXR to influence 3α,5α-THP production from central biosynthesis, and/or metabolism of peripheral P4, in the VTA, as well as its role to facilitate, or be increased by, affective/social behaviors is under investigation. Investigating novel behavioral functions of 3α,5α-THP extends our knowledge of the neurobiology of progestogens, relevant for affective/social behaviors, and their connections to systems that regulate affect and motivated processes, such as those important for stress regulation and neuropsychiatric disorders (anxiety, depression, schizophrenia, drug dependence). Thus, further understanding of 3α,5α-THP’s role and mechanisms to enhance affective and motivated processes is essential.